Developing a model for investigating one-to-one synchronous Chinese online language teaching via videoconferencing. Issue 1 (14th March 2021) - White, Cynthia; Zheng, Yanqun; Skyrme, Gillian
Abstract: Innovation in technology-enhanced language learning environments has been largely driven by the affordances of new tools and rich, smart learning environments alongside the use of everyday tools. Such technology-mediated environments open up further ways of researching and enhancing language learning and call for new methodological and conceptual tools to support the investigation of learning in productive ways. The focus of this article is to present a model to guide enquiry into and practice within one-to-one synchronous online language teaching via videoconferencing. The model has been derived from an ongoing study undertaken by the authors, so as each element is explained, brief excerpts of data from that study are provided to illustrate the personal, interpersonal and situational complexities that influence teachers' and learners' actions and interactions. The multi-layered nature of the framework uncovers different aspects of the interactions which provide affordances for learning within this multimodal language-learning environment. It draws on key concepts of sociocultural theory, including a situated investigation of agency in relation to language use and environmental factors. We argue that the model we have developed can provide useful conceptual and practical tools to guide enquiry into technology-enhanced language learning environments and teacher awareness of the affordances and emergent complexities of those environments.